Chest Pain in Adolescent Japanese Male Mimicking Acute Coronary Syndrome - Sachin K. Gupta; Zahra Naheed (Case Reports in Critical Care)
Acute chest pain with very elevated troponin level and abnormal EKG in adult population is considered sine qua non to acute coronary syndrome (ACS) unless proved otherwise. Similar presentation in adolescent population is seen less often but raises suspicion for ACS. Most common etiology for chest pain with cardiac enzyme elevation in adolescent population is usually viral myopericarditis. The adolescent population presenting with chest pain and elevated cardiac enzymes should be carefully evaluated for ACS and other etiologies including myocarditis, myopericarditis, pulmonary embolism, acute rheumatic fever, and trauma. We report one Japanese adolescent male with mycoplasma pneumoniae myocarditis who presented to the ER with chest pain, elevated cardiac enzymes, and abnormal EKG.